Il personaggio del padre nella Väterliteratur (ENTHYMEMA, 2020)
This work focuses on the character of the father in the Väterliteratur, a rich production of the German-language literature mostly composed of (auto)biographical texts. While recent studies have been interested in issues concerning the genre and its story, this essay pays attention to the literary constitution of the partly biographical, partly fictional character of the father. By means of examples contained in some novels, the recurring motifs and the narrative structure of the Väterbücher are thus illustrated, as well as the close connection between the fatherly figures and their son-narrators, who tell the biography of the fathers relying on heterogeneous sources. Starting from some metaliterary considerations contained in the texts, it is finally shown how the father figure provides valuable insight into themes such as the relationship between life and writing, person and character, documentable experience and fiction.